Estructuras urbanas : trazados y laberintos (2017)
The thesis Project is a reflection of the city from the concept of Urban Structure. The Project attempt to create a procedural manifest base don the conception of an urban structure, reinterpreting the city for establishing analogy with the labyrinth and the tower as archetypal structures. The Project is located in the Localidad de Chapinero of Bogotá, between the 57 to 59 street and Avenida Caracas and 7th road. Starting from the situationistpostulates and some iterature fragments, it is developed a procedure to projectan urban structure with labyrinthic characteristics and an orientation system based on the sun, which guide throw meeting spaces. The labyrinth tries to disorientate, hiding an orientation language of fragmatic origin, taking the human back to an own-time in relation with the stars. In this way, the project procedure overlap different stroke systems to conform the project program. Being a project of mixed uses, at first place...